(untitled) (Research, Society and Development, 2021)
Objective: to analyze the evolution of confirmed cases of sporotrichosis in the municipality of Timbaúba - PE using Regression and Prediction Models. Method: monthly data of confirmed cases of sporotrichosis were used through clinical and laboratory tests, provided by an Animal Health Unit, from January to December 2020. With the data, statistical tests were performed with the Regression Models: linear simple, cubic and quadratic. In addition to prediction tests with the Simple Average Model. Results: the analysis of the Cubic Regression Model demonstrated the best fit for the data set of confirmed cases of sporotrichosis in the municipality. Conclusion: with the analysis it was possible to perceive the oscillation around 3 confirmed cases, with no trend of change, whose forecast for the month of January 2021 lies in the evidence of the occurrence of 2.66 cases at 95% confidence.